2019
DOI: 10.1038/s41598-019-52208-3
|View full text |Cite|
|
Sign up to set email alerts
|

Osteopontin Expression in Small Airway Epithelium in Copd is Dependent on Differentiation and Confined to Subsets of Cells

Abstract: Osteopontin (OPN) plays a role in inflammation via recruitment of neutrophils and tissue remodeling. In this study, we investigated the distribution of OPN-expressing cells in the airway epithelium of normal lung tissue and that from patients with chronic obstructive pulmonary disease (COPD). OPN was detected on the epithelial cell surface of small airways and in scattered cells within the epithelial cell layer. Staining revealed higher OPN concentrations in tissue showing moderate to severe COPD compared to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…On the other hand, SPP1 is associated with neutrophilic inflammation and emphysema [30]. Cigarette smoking can increase SPP1 expression in induced sputum, and its level is increased in induced sputum [31] and lung tissue [32] of patients with COPD. Hence, SPP1 may participate in the pathogenesis of COPD.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, SPP1 is associated with neutrophilic inflammation and emphysema [30]. Cigarette smoking can increase SPP1 expression in induced sputum, and its level is increased in induced sputum [31] and lung tissue [32] of patients with COPD. Hence, SPP1 may participate in the pathogenesis of COPD.…”
Section: Discussionmentioning
confidence: 99%
“…OPN contributes to processes of tissue remodeling and EMT during tumor progression, for example, renal tubular epithelial cells, hepatocellular carcinomas, or breast carcinomas 15,16 . Our previous studies demonstrated that OPN gene and protein overexpressed in acute exacerbation of chronic obstructive pulmonary disease and lung cancer are probably responsible for evolution and heterogeneity of lung cancer 17,18 . OPN overexpression was considered as an independent prognostic factor in patient overall survival and associated with more aggressive phenotypes of patients with lung cancer, 19 although the molecular mechanisms are still unclear.…”
Section: Introductionmentioning
confidence: 99%
“…It can be alternatively spliced to produce a variety of local functions, such as tumor growth, invasion, metastasis, angiogenesis, drug resistance, and immunosuppression. It is widely expressed in bone, kidney, breast, thymus, the immune system, and the brain ( 16 ). The most versatile subtype in tumor tissue is β3 ( 17 ), which is related to growth, invasion, metastasis, and survival.…”
Section: Discussionmentioning
confidence: 99%